Comparison of Early and Delayed Feeding after Elective Gut Anastomosis - Ghazanfar Jabbar; Mirza Sijeel Ahmed; Arsalan Sharif Malik; Shahzad Akhtar; Farooq Sultan Minhas; Muhammad Talha Makshoof; Zoha Shahid (Life and Science, 2024)
Objective: To compare the effects of early and delayed feeding after elective gut anastomosis in relation to a mean number of days of audible bowel sounds. Study Design: A cross-sectional study. Place and Duration of Study: The study was conducted at the Department of Surgery, Combined Military th th Hospital (CMH), Rawalpindi, Pakistan, from 11th May 2019 to 10th November 2019. Methods: A total of 60 individuals undergoing gut anastomosis were divided into two groups. In group A, the NG tube was removed within 6 to 24 hours of surgery, and clear oral liquids (30ml/hour) were started. Oral fluids, including juices and soups on the other day after surgery, tailed by semisolid food at 3rd day, then regular food at 4 day and finally discharge at the 5 day. In group B, the NG tube was detached three to five days after the procedure, observing NG tube output <30-50cc daily. Then, patients were followed up in post-surgical wards for 48 hours. Patients were noted and informed of the time when bowel sounds were audible, the first flatus passed, and the first stool passed. Results: The mean age in group A was 40.23 ± 15.66 years, and in group B was 37.93 ± 15.23 years. Most of the patients, 31 (51.67%), were between 16 to 30 years of age. Out of 60 patients, 36 (60.0%) were males and 24 (40.0%) were females, with male to female ratio of 1.5:1. The mean number of days of audible bowel sounds in Group A (early feeding) was 1.57 ± 0.63 days while in Group B (delayed feeding) was 3.90 ± 0.76 days (p-value = 0.0001). Conclusion: This research established that the outcome of early feeding is better than the outcome of delayed feeding after elective gut anastomosis.